Ethnic Concentration and Human Capital Formation - Thomas de Graaff; Henri L.F. de Groot (Tinbergen Institute, 2004)
Concentration of immigrants and its associated externalities have become an important topic in contemporary international migration research, both from a methodological as well as an empirical perspective. The purpose of this paper is twofold. First, it aims to provide an overview of that part of the migration literature that is concerned with the externalities created by the influx of immigrants. Second, it presents a stylized model in which human capital accumulation and ethnic cluster formation are explicitly incorporated. The model shows that lock-in effects can result from heterogeneous human capital and spillover effects on different spatial levels. Extensions of the model are discussed, together with their possible impacts on the spatial variation of the evolution of human capital stocks.
Keywords: J61; R11; 330; Ethnic concentration; human capital; migration; migration costs; Ethnische Gruppe; Humankapital; Migranten; Segregation